Anoxic carbon flux in photosynthetic microbial mats as revealed by metatranscriptomics - Burow, Luke C (Nature Publishing Group, 2013)
Photosynthetic microbial mats possess extraordinary phylogenetic and functional diversity that makes linking specific pathways with individual microbial populations a daunting task. Close metabolic and spatial relationships between Cyanobacteria and Chloroflexi have previously been observed in diverse microbial mats. Here, we report that an expressed metabolic pathway for the anoxic catabolism of photosynthate involving Cyanobacteria and Chloroflexi in microbial mats can be reconstructed through metatranscriptomic sequencing of mats collected at Elkhorn Slough, Monterey Bay, CA, USA. In this reconstruction, Microcoleus spp., the most abundant cyanobacterial group in the mats, ferment photosynthate to organic acids, CO(2) and H(2) through multiple pathways, and an uncultivated lineage of the Chloroflexi take up these organic acids to store carbon as polyhydroxyalkanoates. The metabolic reconstruction is consistent with metabolite measurements and single cell microbial imaging with fluorescence in situ hybridization and NanoSIMS.